Institute of Dispute Resolution by the Participation of a Judge in the Court of Ukraine: Joint and Different Characteristics with the Institute of Mediation in Ukraine - KARMAZA, Oleksandra O.; STEFANYSHYN, Nataliia M.; SKHAB-BUCHYNSKA, Tetiana Ya.; KOROIED, Sergii O. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The relevance of this article is explained by the fact that in 2017 a new procedural institute – dispute resolution by the participation of a judge was introduced into the legal science of Ukraine, as well as in the judicial practice of Ukraine. In the jurisprudence of Ukraine, there is no consensus on the unity or difference between the institute of mediation in Ukraine and the institute of dispute resolution by the participation of a judge in Ukraine. The purpose of the article is the scientific and practical analysis of the norms of the Civil Procedural Code of Ukraine, the Commercial and Procedural Code of Ukraine and the Code of Administrative Proceedings of Ukraine in terms of determining the procedure for resolving a dispute by the participation of a judge, as well as determining the common and distinctive features of the mediation institute and the institute of dispute resolution by the participation of a judge under Ukrainian law. The article proposes improvements of Ukrainian legislation.